THE IMPACT OF PERCEIVED ORGANIZATIONAL SUPPORT, LEADERSHIP, AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE - Ulfa Rahmawati; Elly Joenarni; Anna Kridaningsih; Zenita Afifah Fitriani (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
This study examines how perceived organizational support, leadership, and work motivation affect on employee performance. The unit of analysis used is the employees at the company CV. Amanah. This study included all employees. This study randomly selected 18 people. This study uses primary and secondary sources. The validity and reliability test, classic assumption test, multiple linear regression test, and hypothesis test were used in this study. Perceived organizational support, leadership, and work motivation partially and concurrently affected employee performance. Even if the effect was somewhat meaningful, motivates workers and affects UD performance.